Pengembangan Bahan Ajar Komik Cerita Rakyat Berbasis Problem Based Learning Menggunakan Aplikasi Adobe Illustrator untuk Meningkatkan Hasil Belajar Kognitif pada Pembelajaran Bahasa Indonesia Kelas 2 SD - Purwansyah, Dodi; Gumono; Muktadir, Abdul (Jurnal Kajian Pendidikan Dasar, 2025)
This study aims to develop folktale comic teaching materials based on Problem-Based Learning (PBL) using Adobe Illustrator to enhance cognitive learning outcomes in Indonesian language learning for 2nd-grade elementary school students. The research method used is Research and Development (R&D) with the ADDIE model. The research subjects consist of teachers and students of Grade 2 at SDN Transpangkalan. Data collection was conducted through needs analysis, observation, interviews, and cognitive learning outcome tests, with data analysis performed qualitatively and quantitatively. The research results show that the development of teaching materials was systematically carried out based on curriculum analysis and student needs. Validation results indicated an increase in feasibility: the content aspect improved from 0.50 (moderate) to 0.90 (highly valid), the language aspect from 0.57 (moderate) to 1.00 (highly valid), and the design aspect from 0.50 (moderate) to 0.87 (highly valid). Teacher and student responses also indicated that the teaching material is engaging and suitable for use in learning. The effectiveness of this teaching material was proven by an N-Gain increase in the experimental class of 0.47 (moderate category) compared to the control class, which only increased by 0.22 (low category). The Independent t-Test showed a significance value of 0.000 (p < 0.05), indicating a significant difference in student learning outcomes. Thus, the folktale comic-based PBL teaching material positively contributes to improving students' cognitive learning outcomes in 2nd-grade elementary school Indonesian language learning.